Microtube Irrigation For Banana Cultivation in South Bihar: Participatory Assessement and Refinement - Bhatnagar, P R; Sikka, A K; Gautam, U S; Singh, S S; Kumar, Ujjwal; Rajan, K (Journal of Agricultural Engineering, 2007)
To evaluate the efficacy of drip irrigation to improve production and quality of horticultural crops in humid region of eastern India, a participatory study was carried out at four locations in Patna district (Bihar, India) with banana as target crop. Initially, the system was laid out as per conventional design having TABE (take apart button emitter) with 12mm lateral which gave 7.2 I/h discharge with coefficient of variation of 54%. The system was refined to improve its performance and reduce the cost as per need and perception of the farmers. Farmers expressed one TABE per plant insufficient and hence, TABE were replaced with newly designed star microtube emitters, which delivered water at four points in a circle of 25 cm diameter around a plant. Adecreasing trend in the discharge along lateral was observed which was rectified by replacing the lateral with 16mm lateral. The system had better performance with less discharge variations and cheap as compared to conventional system. The system was tested with two varieties of banana: Alpan and dwarf Cavendish. Farmers were satisfied with the refinements and realized advantages of drip irrigation in early shooting and bunch emergence, better finger size and bunch size, and better returns. Considering annualised cost of the drip system and benefits due to improved production only, the B-C ratio was 1.01 to 1.87 for var. Alpan and 1.61 to 1.75 for var. dwarf Cavendish.